Assessment of the risk of contact fatigue damage in wheels and rails using the Dang Van criterion - V. I. Sakalo; A. V. Sakalo (Вестник Научно-исследовательского института железнодорожного транспорта)
Introduction. Dynamic loads cause high contact stresses in the materials of wheels and rails, which leads to their wear and accumulation of contact fatigue damage. A number of approaches were proposed for calculations of contact fatigue and prediction of damage accumulation processes. One of them uses the Dang Van criterion. It involves time-consuming iterative procedures, so it is used to assess contact fatigue at individual points of wheel and rail. In order to simplify calculations and obtain more extensive information, the authors proposed an engineering method that allows determining the risk of contact fatigue damage for sub-contact layer nodes represented by a finite element model, with an unlimited number of wheel — rail contact implementations.Materials and methods. The approach is based on the use of the Dang Van criterion with the introduction of some assumptions. The amplitude of the largest shear stresses is taken as the amplitude of the shear stresses. The components of technological and operational residual stresses are set using the results of experimental studies or those obtained by calculation methods. Information about wheel — rail contact conditions was obtained by modeling of the vehicle movement. Calculations were performed considering changes in wheel and rail profiles during the modeling process caused by wear. Results. The test results were obtained for some cases of wheel — rail contact, as well as for determining the contact fatigue damage risk indicator for the wheel and rail with a sufficiently large number of contact implementations. The calculation results are presented in the form of isolines of the value of indicator for the points of the layer adjacent to the tread surfaces.Discussion and conclusion. The proposed approach can be used to determine the risks of contact fatigue damage in railway wheels and rails, in particular, to optimise wheel and rail profiles according to wear and contact fatigue criteria.